1982
DOI: 10.1159/000166629
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Dysfunction and Impotence in Uremia

Abstract: The relationship between abnormalities in nocturnal penile tumescence (NPT) and autonomic function, measured by the Valsalva maneuver, was evaluated in 25 uremic patients and 22 normal subjects. NPT in uremic patients (45 ± 6.8 min/night) was lower (p < 0.01) than in normals (85 ± 10.4 min/night). Valsalva ratio in uremics (1.58 ± 0.07) was also lower (p < 0.01) than in normal subjects (2.05 ± 0.11). NPT and Valsalva ratio were significantly correlated in uremic patients (r = 0.62, p < 0.01). The 12 uremic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
4

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 1 publication
0
12
1
4
Order By: Relevance
“…Previous studies of the effect of dialysis on plasma noradrenaline levels have produced conflicting results [1,41]. The finding of elevated plasma noradrenaline levels at rest conflicts with previous obser vations [42], The absence of an effect of haemodialysis on plasma noradrenaline in the present study suggests that sympathetic nervous activity is not impaired as a conse quence of haemodialysis and that depletion of plasma noradrenaline is unlikely to be a contributory factor to haemodialysis-induced hypotension. Alternatively, the absence of a rise in plasma noradrenaline when extracel lular fluid volume had been reduced by haemodialysis may be a pointer to reduced sympathetic efferent activity.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies of the effect of dialysis on plasma noradrenaline levels have produced conflicting results [1,41]. The finding of elevated plasma noradrenaline levels at rest conflicts with previous obser vations [42], The absence of an effect of haemodialysis on plasma noradrenaline in the present study suggests that sympathetic nervous activity is not impaired as a conse quence of haemodialysis and that depletion of plasma noradrenaline is unlikely to be a contributory factor to haemodialysis-induced hypotension. Alternatively, the absence of a rise in plasma noradrenaline when extracel lular fluid volume had been reduced by haemodialysis may be a pointer to reduced sympathetic efferent activity.…”
Section: Discussioncontrasting
confidence: 93%
“…clinical disorders and normal renal function do not dis play evidence of ANS dysfunction [5]. It appears that anemia of CRF does not play a major role in the genesis of ANS dysfunction.…”
Section: Resultsmentioning
confidence: 88%
“…It appears that anemia of CRF does not play a major role in the genesis of ANS dysfunction. Campese et al [5] found no signif icant difference in the values of hematocrit of CRF and dialysis patients with and without ANS dysfunction. Our data also show that hematocrit values in dialysis patients with volume-responsive or volume-nonresponsive hypo tension were not significantly different.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The simultaneous occurrence of pheochromo- To the authors' knowledge, determination of excretory end products of CA metabolism in the plasma of such patients has not been reported. Moreover, interpretation of plasma CA is impaired, as patients on long-term hemo dialysis (LTH) without pheochromocytoma already have an altered CA status as compared with a normal popula tion, and a 'normal' range of plasma CA for LTH patients has not been unequivocally established [9][10][11][12][13][14][15][16][17][18][19],…”
Section: Introductionmentioning
confidence: 99%